PENGARUH NON-LINIERITAS GURU TERHADAP KOMPETENSI BELAJAR SISWA DI MA SAFINDA SURABAYA - WULANDARI, OVI; NATASYA, RIZKI DWI; MASITHOH, ARINA DEWI; FUAD, AH. ZAKKI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This research aims to analyze whether there is an influence of non-linear teachers (who teach outside their field) on student learning competence at MA Safinda Surabaya. This research uses a quantitative approach with a questionnaire as the main instrument for data collection. The research instrument was created referring to aspects of learning theory according to Edgar Dale, who stated that there are 10 important aspects, namely;Read, Hear, View Images, Watch Videos, Attend Exhibitis/Sites, Watch a Demonstration, Participate in Hands-On-Workshops, Design Collaborative Lesson, Simulate and Design/Perform a Presentation. Data from the questionnaire results were analyzed using a simple regression test to assess the relationship between the independent variable (non-linear teacher) and the dependent variable (student learning competency). The results of the analysis show that the significance value (sig) is 0.007, so 0.007 > 0.05, which means Ho is accepted and Ha is rejected. Therefore, it can be concluded that there is no significant influence of teacher non-linearity on student learning competence at MA Safinda Surabaya. This shows that even though teachers do not have a background appropriate to their field, they still have the opportunity to take part in training or other self-development activities which will later haveimpact positive impact on student learning competence. ABSTRAKPenelitian ini bertujuan untuk menganalisis ada tidaknya pengaruh guru non-linier (yang mengajar di luar bidangnya) terhadap kompetensi belajar siswa di MA Safinda Surabaya. Penelitian ini menggunakan pendekatan kuantitatif dengan angket sebagai instrumen utama dalam pengumpulan data. Instrumen penelitian di buat merujuk pada aspek teori belajar menurut Edgar Dale, yang mengemukakan bahwa terdapat 10 aspek penting yaitu; Read, Hear, View Images, Watch Videos, Attend Exhibitis/Sites, Watch a Demonstration, Participate in Hands-On-Workshops, Design Collaborative Lesson, Simulate and Design/Perform a Presentation. Data dari hasil angket di analisis menggunakan uji regresi sederhana untuk menilai hubungan antara variabel bebas (guru non-linier) dan variabel terikat (kompetensi belajar siswa). Hasil analisis menunjukkan bahwa nilai signifikansi (sig) sebesar 0,007, maka 0,007 > 0,05, yang artinya Ho diterima dan Ha ditolak. Oleh karena itu, dapat disimpulkan bahwa tidak ada pengaruh yang signifikan dari non-linieritas guru terhadap kompetensi belajar siswa di MA Safinda Surabaya. Hal ini menunjukkan bahwa meskipun guru tidak memiliki latar belakang yang sesuai dengan bidangnya, mereka tetap memiliki kesempatan untuk mengikuti pelatihan atau kegiatan pengembangan diri lainnya yang nantinya dapat memiliki impact positif pada kompetensi belajar siswa.